Small molecule allosteric modulation of the adenosine A1 receptor - Nguyen, Anh T. N.; Tran, Quan L.; Baltos, Jo-Anne; McNeill, Samantha M.; Nguyen, Diep T. N.; May, Lauren T. (Frontiers in Endocrinology, 2023)
G protein-coupled receptors (GPCRs) represent the target for approximately a third of FDA-approved small molecule drugs. The adenosine A1 receptor (A1R), one of four adenosine GPCR subtypes, has important (patho)physiological roles in humans. A1R has well-established roles in the regulation of the cardiovascular and nervous systems, where it has been identified as a potential therapeutic target for a number of conditions, including cardiac ischemia-reperfusion injury, cognition, epilepsy, and neuropathic pain. A1R small molecule drugs, typically orthosteric ligands, have undergone clinical trials. To date, none have progressed into the clinic, predominantly due to dose-limiting unwanted effects. The development of A1R allosteric modulators that target a topographically distinct binding site represent a promising approach to overcome current limitations. Pharmacological parameters of allosteric ligands, including affinity, efficacy and cooperativity, can be optimized to regulate A1R activity with high subtype, spatial and temporal selectivity. This review aims to offer insights into the A1R as a potential therapeutic target and highlight recent advances in the structural understanding of A1R allosteric modulation.